Generation and Use of a Digest System by Integrating OCR and Smart Searches - Cáseres, Germán (2017)
A digest can be defined as a regulations repository which is manipulated by organizations for extended time periods. The search for information in this repositories can be tedious without assistance from an adhoc software application. This work presents the development of a Digest Software System with its architecture and integration with other base tools. Finally, two study cases are presented where the developed product is used.